Comparative Study of Different Division Algorithms for Fixed and Floating Point Arithmetic Unit for Embedded Applications - Rohini S, Hongal; Anita, DJ (International Journal of Computer Sciences and Engineering, 2025)
ALU is very essential unit of any embedded processors. Very basic operations like addition, subtraction, multiplication and division are part of ALU unit. In literature, we have many algorithms to perform addition, subtraction and multiplication but less on division algorithm. The division algorithm performs, either by addition or subtraction, based on the signs of the divisor and partial remainder. Floating point division is considered as a high latency operation. Division algorithms have been developed to reduce latency and to improve the computational efficiency, hardware cost, area and power of processors. This paper presents different division algorithms such as Digit Recurrence Algorithm restoring, non-restoring and SRT Division (Sweeney, Robertson, and Tocher), Multiplicative Algorithm, Approximation Algorithms, CORDIC Algorithm and Continued Product Algorithm. This paper intended to compare various techniques used and their features relevant for various applications.